The anti-proliferative effect of apricot and peach kernel extracts on human colon cancer cells in vitro - Wagheda Cassiem; Maryna de Kock (BMC, 2019)
Abstract Background Colorectal malignant neoplasms is one of the leading causes of death in both men and women in the developed world and the incidence has recently increased markedly in South Africa. Studies have highlighted the beneficial effects of Amygdalin, a cyanogenic compound found in both peach and apricot kernels, in its ability to suppress the development of colon cancer. The focus of this study was to investigate the potential anti-proliferative properties of various apricot and peach kernels extractions from South Africa and China and to monitor alterations in cell cycle kinetics in colon cancer cells. Methods Studies were conducted on HT-29 colon cancer cells. The interactive role of three different kernel extractions on the modulation of cell proliferation, apoptosis and cell cycle progression was monitored over 24, 48 and 72 h periods. Results After 24 h, all extracts of the South African apricot kernels had a dose related bi-phasic proliferative effect on the HT-29 cells. It stimulated cell proliferation at the lowest and highest concentrations while at 500 μg/mL it inhibited cell proliferation. In contrast, after 72 h, the low concentration inhibited cell proliferation while the 500 μg/mL extracts stimulated cell proliferation. Morphological changes were observed in cells incubated with Chinese kernel extracts after 24 h and South African kernel treatment (1000 μg/mL) after 72 h. A possible intra-S-phase block after 24 and 48 h exposure to South African hydrophilic kernel extracts was observed. This transient block that is more concerned with tolerating and accommodating damage during replication rather than repairing it, could explain the initial anti-proliferative effects observed after 24 h exposure to the various Chinese kernel extract concentrations. Conclusion Abrogation of the block by exhaustion of the cyanide production, most likely allowed the cells to resume the cell cycle and continue into mitosis, whereas low ATP levels caused by the presence of amygdalin in the kernels, can also cause the induction of pycnosis or necrosis. These results highlight the possible mechanisms of growth inhibition by amygdalin containing extracts and may contribute towards the development of dietary anti-cancer therapies.